High-temperature-impact-resistant flux-cored wire and preparation method thereof

By preparing flux-cored welding wire containing specific raw materials, the problems of impact resistance at high temperatures and stability at low temperatures have been solved, enabling the efficient use of welding wire in the metallurgical industry and improving the overall applicability of welds.

CN121199461AInactive Publication Date: 2025-12-26SHENGYANG HAWEIER SURFACE ENG TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511579419.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2025-12-26
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing flux-cored welding wires have insufficient impact resistance and weld tensile strength at high temperatures above 800℃, and poor freezing stability at low temperatures, which limits their efficiency and effectiveness in the metallurgical industry.

Method used

High-temperature impact resistant flux-cored welding wire is prepared by using raw materials such as chromium carbide powder, molybdenum powder, nickel powder, niobium powder, and tungsten carbide powder, and adding modified titanium carbide agent and boron-based additives through low-speed and high-speed mixing, rolling, and drawing steps. Stable alloy carbides and intermetallic compounds are formed to enhance the weld microstructure. In combination with basalt fiber and mullite whiskers, a skeleton structure is formed to improve high-temperature tensile strength.

Benefits of technology

It significantly improves the impact resistance and weld tensile strength of flux-cored welding wire in high-temperature environments, while maintaining stability at low temperatures, adapting to the complex service environment of the metallurgical industry, extending the service life of components and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure MS9R1KMOFOCYQ8DTPJJRBUTGMJALP1FXAUU5JRNM
    Figure MS9R1KMOFOCYQ8DTPJJRBUTGMJALP1FXAUU5JRNM
  • Figure QZ5X0RZS8GWJYTITMGG7AYJ2EZ6NWRZNS1HC6Y8Y
    Figure QZ5X0RZS8GWJYTITMGG7AYJ2EZ6NWRZNS1HC6Y8Y
Patent Text Reader

Abstract

The invention relates to the technical field of flux-cored wires. The preparation method comprises the following steps: weighing the following raw materials in parts by weight: 4-6 parts of chromium carbide powder, 7-9 parts of molybdenum powder, 6-8 parts of nickel powder, 10-15 parts of niobium powder, 15-18 parts of tungsten carbide powder, 7-11 parts of a modified titanium carbide agent, 5-8 parts of a blending agent added based on boron and 2-4 parts of 30-mesh natural graphite; 1-2 parts of sodium fluosilicate; 1-2 parts of aluminum powder; and 70-75 parts of iron powder. The flux-cored wire can adapt to complex service environments of parts such as rollers and continuous casting crystallizers in the metallurgical industry, the service life of the parts subjected to surfacing repair is prolonged, the production efficiency of the parts subjected to surfacing repair is improved, the obtained flux-cored wire achieves balance of high-temperature performance, mechanical performance and low-temperature stability, and the comprehensive applicability of products is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of flux-cored wire, in particular to a high-temperature impact-resistant flux-cored wire and a preparation method thereof. BACKGROUND

[0002] As the core link of the basic industry, the production process of the metallurgical industry depends on key equipment such as rolling, continuous casting, heating furnace, etc., and the service performance of core components such as rolls, continuous casting crystallizers, heating furnace bottom rolls, blast furnace chute, etc. directly determines the production efficiency, product quality and comprehensive cost. The surfacing repair and strengthening demand of metallurgical components is the mainstream direction of current research. At present, in the metallurgical industry, the flux-cored wire used in the high-temperature environment above 800 DEG C has defects such as poor impact resistance, poor weld tensile strength, poor freezing stability in low-temperature environment, and poor comprehensive coordination of the product, which limits the use efficiency of the product. Based on this, the present application further improves the product. SUMMARY

[0003] In view of the defects of the prior art, the purpose of the present application is to provide a high-temperature impact-resistant flux-cored wire and a preparation method thereof to solve the problems raised in the background art.

[0004] The technical problem solved by the present application adopts the following technical scheme: The present application provides a preparation method of a high-temperature impact-resistant flux-cored wire, comprising the following steps: Step one: weigh the raw materials according to the weight parts: chromium carbide powder 4-6 parts, molybdenum powder 7-9 parts, nickel powder 6-8 parts, niobium powder 10-15 parts, tungsten carbide powder 15-18 parts, modified titanium carbide agent 7-11 parts, blending agent based on boron addition 5-8 parts, 30 mesh natural graphite 2-4 parts, sodium fluosilicate 1-2 parts, and aluminum powder 1-2 parts and iron powder 70-75 parts; Step two: first, add chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder, modified titanium carbide agent, blending agent based on boron addition, 30 mesh natural graphite and iron powder into a double-cone mixer, mix at low speed for 30-40 min, mixing speed 100-150 r / min, then add sodium fluosilicate and aluminum powder, mix at high speed for 15-20 min, mixing speed 750-850 r / min, and argon gas is introduced during the mixing process; Step three: fill the mixed flux core powder of step two into a U-shaped steel belt slot, control the flux core filling rate to be 38-42%, and immediately roll into shape after filling; Step four: then adopt drawing treatment, and finally dry the drawn wire in a vacuum oven at 120-125 DEG C for 2-3 h.

[0005] Preferably, the drawing treatment adopts 10 passes, each pass deformation rate is 12%, and the drawing is performed to a finished product diameter of 1.2 mm.

[0006] Preferably, the preparation method of the modified titanium carbide agent is: S01, preparation of the modification liquid: S02, preheat the titanium carbide at 55-60℃ for 1h to obtain preheated titanium carbide, and then stir and modify the preheated titanium carbide and the modification liquid at a weight ratio of 3:(5-8), and after the stirring is completed, obtain the titanium carbide modification liquid; S03, stir the basalt fiber in a sufficient amount of a 10-15% mass fraction potassium permanganate solution, and then wash with water, filter, and dry; Blend 3-5 parts of dried basalt fiber, 2-4 parts of mullite whiskers, and 2-3 parts of wollastonite with 10-15 parts of a sodium lignosulfonate solution, and then filter and dry to obtain a basalt fiber filler; S04, ball mill the titanium carbide modification liquid and the basalt fiber filler at a weight ratio of (8-11):5, at a ball milling speed of 1000-1500r / min, for 2h, and after the ball milling is completed, filter and dry to obtain the modified titanium carbide agent.

[0007] Preferably, the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring time is 2h; and the mass fraction of the sodium lignosulfonate solution is 10-15%.

[0008] Preferably, the preparation method of the modification liquid is: S01a, blend and sinter 5-8 parts of silicon dioxide, 3-5 parts of petalite, and 2-4 parts of nano lanthanum oxide, and after the sintering is completed, obtain a sintered body; Blend 2-4 parts of a silane coupling agent KH550, 1 part of β-cyclodextrin, and 5-7 parts of a 75-85% mass fraction ethanol solution at a weight ratio of (2-4):1:(5-7) to obtain a silane coupling agent-β-cyclodextrin agent; S01b, blend 5-8 parts of a sodium citrate solution, 2-3 parts of zinc oxide, and 0.3-0.5 parts of a nano silicon sol uniformly, and then add 3-5 parts of the silane coupling agent-β-cyclodextrin agent to continue blending to obtain a modified sodium citrate liquid; S01c, stir the sintered body and the modified sodium citrate liquid uniformly at a weight ratio of 5:(8-11) to obtain a modification liquid.

[0009] The modified titanium carbide agent is prepared by ball milling of a titanium carbide modification liquid and a basalt fiber filler. The titanium carbide in the titanium carbide modification liquid is preheated, and then the modification liquid is improved and optimized. The silane coupling agent-beta cyclodextrin agent in the modification liquid can adjust the sodium citrate solution raw material, and optimize the interface bonding of zinc oxide and sintered body in the system. At the same time, the silica, petalite and nano lanthanum oxide in the sintered body are matched with the titanium carbide in the system, which can optimize the performance coordination of the system. The nano lanthanum oxide refines the grain and inhibits the grain growth of titanium carbide at high temperature, so that the titanium carbide can still maintain a stable hard phase structure at a high temperature environment above 800 DEG C. The coordination of silica and petalite fills the system structure and enhances the performance coordination and stability of the system. At the same time, the basalt fiber filler is improved by basalt fiber, mullite whisker, wollastonite and sodium lignosulfonate solution, which has a filling and strengthening effect. After the basalt fiber is treated by potassium permanganate oxidation, active groups such as hydroxyl groups are introduced on the surface. The basalt fiber, mullite whisker and wollastonite form a "fiber-whisker-mineral" composite filler through the dispersion of sodium lignosulfonate. The basalt fiber (high temperature resistant and high strength) and mullite whisker (high hardness and thermal shock resistance) act as the "skeleton", and the wollastonite (low expansion coefficient) relieves the thermal stress at high temperature. The three are closely combined with titanium carbide through ball milling to form a "hard phase + reinforcing phase" synergistic structure, which significantly improves the high temperature impact resistance and tensile strength of the weld.

[0010] Preferably, the sintering time of the blended sintering is 1-1.5h, and the sintering temperature is 300-350℃.

[0011] Preferably, the preparation method of the blending agent based on boron addition is: S11, 3-5 parts of yttrium nitrate solution, 2-4 parts of carbon nanotube and 1-3 parts of titanium oxide are uniformly blended, then 35-40% of boron oxide of the total amount of the blended material is added to the blended material, ball milling treatment, ball milling speed 1000-1500r / min, ball milling 2h, after ball milling, a boron-based composite liquid is obtained; S12, the sodium alginate solution is stirred uniformly by adding sodium silicate solution and hydroxyapatite, and a sodium alginate agent is obtained; 3-5 parts of barium sulfate, 2-4 parts of mica powder and 5-9 parts of sodium alginate agent are stirred fully, then filtered and dried to obtain a blending additive; S13, the boron-based composite liquid and the blending additive are mixed according to the weight ratio (7-11):5, ball milling treatment, ball milling speed 1500-1700r / min, ball milling 2h, after ball milling, the blending agent based on boron addition is obtained by filtering and drying.

[0012] The boron-added blending agent is improved by ball milling based on a boron-based composite liquid, a blending additive, the boron-based composite liquid is prepared by blending boron oxide, yttrium nitrate solution, carbon nanotubes and titanium oxide, and the performance effect of the system is improved by mutual enhancement. The boron oxide reacts with alloy elements such as nickel and niobium in the flux core in the high-temperature welding process, forms dispersed borides, the borides are enriched at the grain boundary of the weld, can significantly strengthen the grain boundary strength, inhibit the sliding and weakening of the grain boundary at high temperature, thereby improving the impact toughness and tensile strength of the weld in the environment above 800 DEG C, the high aspect ratio and high toughness of the carbon nanotube and the uniform dispersion of the titanium oxide in the boron-based composite liquid can form a "nano-enhanced network" in the weld, further relieve stress concentration and low-temperature stability during high-temperature impact; meanwhile, the sodium alginate in the blending additive is prepared by blending sodium alginate solution, sodium silicate solution and hydroxyapatite, and the performance effect of the product is further improved in the system by the mutual enhancement of the co-blending and re-blending of barium sulfate and mica powder, and the performance of the product is further improved by the better coordination effect of the boron-added blending agent and the modified titanium carbide agent.

[0013] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 5-7%; and the mass fraction of the sodium silicate solution is 4-6%.

[0014] Preferably, the mass ratio of the sodium alginate solution, the sodium silicate solution and the hydroxyapatite is (8-12):(4-7):3.

[0015] The application further provides a high-temperature impact-resistant flux-cored wire prepared by the preparation method.

[0016] Compared with the prior art, the application has the following beneficial effects: The core wire of the application adopts chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder and other raw materials, and simultaneously adds modified titanium carbide agent, blending agent raw materials based on boron addition, mutual cooperation and synergistic effect, the obtained core wire has remarkable impact resistance, weld tensile strength effect, and excellent temperature resistance stability of the core wire under high temperature environment, and the product has obvious freezing stability effect under low temperature environment; the core component of the core wire contains hard phases such as chromium carbide and tungsten carbide, and is matched with alloy elements such as molybdenum, nickel and niobium, which can form stable alloy carbide and intermetallic compound under high temperature, these substances can strengthen the weld structure, effectively resist impact load under high temperature, and avoid cracking or failure of the part under high temperature working condition; the elements such as niobium and nickel can refine the grain structure under high temperature, and improve the high temperature strength and toughness of the weld, at the same time, the components such as basalt fiber and mullite whisker in the modified titanium carbide agent can form a “skeleton” support structure in the weld, further improve the tensile strength under the environment above 800 DEG C, and reduce the risk of deformation or fracture during high temperature service; the synergistic effect of the modified titanium carbide agent and the blending agent based on boron not only strengthens the high temperature mechanical properties, but also takes into account the low temperature stability, avoids the problem of single performance improvement and other performance decline, so that the core wire can adapt to the complex service environment of parts such as rollers and continuous casting crystallizers in the metallurgical industry, improve the service life and production efficiency of the parts after surfacing repair, and the obtained core wire realizes the balance of high temperature performance, mechanical property and low temperature stability, and improves the comprehensive applicability of the product. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the application.

[0018] The preparation method of the high-temperature impact-resistant core wire in the embodiment comprises the following steps: Step one: weigh the raw materials: chromium carbide powder 4-6 parts, molybdenum powder 7-9 parts, nickel powder 6-8 parts, niobium powder 10-15 parts, tungsten carbide powder 15-18 parts, modified titanium carbide agent 7-11 parts, blending agent based on boron addition 5-8 parts, 30 mesh natural graphite 2-4 parts, sodium fluosilicate 1-2 parts, aluminum powder 1-2 parts and iron powder 70-75 parts; Step two: first add chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder, modified titanium carbide agent, blending agent based on boron addition, 30 mesh natural graphite and iron powder into a double-cone mixer, mix at low speed for 30-40 min, mixing speed 100-150 r / min, then add sodium fluorosilicate and aluminum powder, mix at high speed for 15-20 min, mixing speed 750-850 r / min, and argon gas is introduced during the mixing process for protection; Step three: fill the mixed core powder of step two into a U-shaped steel belt slot, control the core filling rate to be 38-42%, and immediately roll into shape after filling; Step four: then use drawing treatment, and finally dry the drawn welding wire in a vacuum oven at 120-125℃ for 2-3h.

[0019] The drawing treatment of this embodiment adopts 10 passes, and the deformation rate of each pass is 12%, and the finished product diameter is 1.2mm.

[0020] The preparation method of the modified titanium carbide agent of this embodiment is: S01, preparation of the modification liquid: S02, preheat the titanium carbide at 55-60℃ for 1h to obtain preheated titanium carbide, and then stir and modify the preheated titanium carbide and the modification liquid according to a weight ratio of 3:(5-8), to obtain a titanium carbide modification liquid; S03, stir the basalt fiber in a sufficient amount of 10-15% mass fraction potassium permanganate solution, then wash with water, filter and dry; Blend 3-5 parts of dried basalt fiber, 2-4 parts of mullite whiskers and 2-3 parts of wollastonite with 10-15 parts of sodium lignosulfonate solution, then filter and dry to obtain a basalt fiber filler; S04, ball mill the titanium carbide modification liquid and the basalt fiber filler according to a weight ratio of (8-11):5, at a ball mill speed of 1000-1500 r / min for 2h, then filter and dry to obtain a modified titanium carbide agent.

[0021] The stirring speed of the stirring modification treatment of this embodiment is 450-550 r / min, and the stirring time is 2h; the mass fraction of the sodium lignosulfonate solution is 10-15%.

[0022] The preparation method of the modification liquid of this embodiment is: S01a, blend and sinter 5-8 parts of silicon dioxide, 3-5 parts of petalite and 2-4 parts of nano lanthanum oxide, and obtain a sintered body after sintering; Blend silane coupling agent KH550, β-cyclodextrin and 75-85% mass fraction ethanol solution according to a weight ratio of (2-4):1:(5-7) to obtain a silane coupling agent-β-cyclodextrin agent. S01b, 5-8 parts of sodium citrate solution, 2-3 parts of zinc oxide and 0.3-0.5 parts of nano-silica sol are uniformly blended, then 3-5 parts of silane coupling agent-beta cyclodextrin agent are added and continue to blend fully, to obtain modified sodium citrate solution; S01c, the sintered body and the modified sodium citrate solution are stirred uniformly according to a weight ratio of 5:(8-11) to obtain a modified solution.

[0023] The sintering time of the blended sintering of the embodiment is 1-1.5h, and the sintering temperature is 300-350℃.

[0024] The preparation method of the blending agent based on boron addition of the embodiment is: S11, 3-5 parts of yttrium nitrate solution, 2-4 parts of carbon nanotubes and 1-3 parts of titanium oxide are uniformly blended, then 35-40% of boron oxide of the total amount of the blended material is added to the blended material, ball milling treatment, ball milling speed is 1000-1500r / min, ball milling for 2h, after ball milling, to obtain a boron-based composite solution; S12, sodium silicate solution and hydroxyapatite are added to the sodium alginate solution and stirred uniformly to obtain a sodium alginate agent; 3-5 parts of barium sulfate, 2-4 parts of mica powder and 5-9 parts of sodium alginate agent are stirred fully, then filtered and dried to obtain a blending additive; S13, the boron-based composite solution and the blending additive are mixed and ball milled according to a weight ratio of (7-11):5, the ball milling speed is 1500-1700r / min, the ball milling time is 2h, after ball milling, the mixture is filtered and dried to obtain a blending agent based on boron addition.

[0025] The mass fraction of the yttrium nitrate solution of the embodiment is 2-5%; the mass fraction of the sodium alginate solution is 5-7%; and the mass fraction of the sodium silicate solution is 4-6%.

[0026] The mass ratio of the sodium alginate solution, the sodium silicate solution and the hydroxyapatite of the embodiment is (8-12):(4-7):3.

[0027] The preparation method of the embodiment is used to prepare a kind of high-temperature impact resistant flux-cored wire.

[0028] Embodiment 1. The preparation method of the high-temperature impact resistant flux-cored wire of the embodiment comprises the following steps: Step one: weigh the raw materials according to the weight parts: chromium carbide powder 4 parts, molybdenum powder 7 parts, nickel powder 6 parts, niobium powder 10 parts, tungsten carbide powder 15 parts, modified titanium carbide agent 7 parts, blending agent based on boron addition 5 parts, 30 mesh natural graphite 2 parts, sodium fluorosilicate 1 part, aluminum powder 1 part and iron powder 70 parts; Step two: first, add chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder, modified titanium carbide agent, blending agent based on boron addition, 30 mesh natural graphite and iron powder into a double-cone mixer, mix at low speed for 30 min, mixing speed 100 r / min, then add sodium fluorosilicate and aluminum powder, mix at high speed for 15 min, mixing speed 750 r / min, and argon gas is introduced during the mixing process for protection; Step three: fill the mixed core powder of step two into a U-shaped steel belt slot, control the core filling rate to be 38%, and immediately roll into shape after filling; Step four: then use drawing treatment, and finally dry the drawn welding wire in a vacuum oven at 120°C for 2h.

[0029] The drawing treatment of this embodiment adopts 10 passes, and the deformation rate of each pass is 12%, and the finished product diameter is 1.2mm.

[0030] The preparation method of the modified titanium carbide agent of this embodiment is: S01, preparation of the modification liquid: S02, preheat the titanium carbide at 55°C for 1h to obtain preheated titanium carbide, and then stir and modify the preheated titanium carbide and the modification liquid according to a weight ratio of 3:5, and obtain the titanium carbide modification liquid after stirring; S03, stir the basalt fiber in a sufficient amount of 10% potassium permanganate solution, then wash with water, filter and dry; Blend 3 parts of dried basalt fiber, 2 parts of mullite whiskers and 2 parts of wollastonite with 10 parts of sodium lignosulfonate solution, then filter and dry to obtain a basalt fiber filler; S04, ball mill the titanium carbide modification liquid and the basalt fiber filler according to a weight ratio of 8:5, at a ball mill speed of 1000 r / min for 2h, filter and dry after ball milling to obtain a modified titanium carbide agent.

[0031] The stirring speed of the stirring modification treatment of this embodiment is 450 r / min, and the stirring time is 2h; the mass fraction of the sodium lignosulfonate solution is 10%.

[0032] The preparation method of the modification liquid of this embodiment is: S01a, blend and sinter 5 parts of silicon dioxide, 3 parts of lithia feldspar and 2 parts of nano lanthanum oxide, and obtain a sintered body after sintering; Blend silane coupling agent KH550, β-cyclodextrin and 75-85% ethanol solution according to a weight ratio of 2:1:5 to obtain a silane coupling agent-β-cyclodextrin agent; S01b, 5 parts of sodium citrate solution, 2 parts of zinc oxide and 0.3 parts of nano-silica sol are uniformly blended, then 3 parts of silane coupling agent-beta cyclodextrin agent are added and uniformly blended to obtain modified sodium citrate solution; S01c, the sintered body and the modified sodium citrate solution are uniformly stirred according to a weight ratio of 5:8 to obtain a modified solution.

[0033] The sintering time of the blended sintering of the embodiment is 1h, and the sintering temperature is 300℃.

[0034] The preparation method of the blending agent based on boron addition in the embodiment is: S11, 3 parts of yttrium nitrate solution, 2 parts of carbon nanotube and 1 part of titanium oxide are uniformly blended, then 35% of boron oxide of the total amount of the blended material is added to the blended material, ball milling treatment is carried out at a ball milling speed of 1000r / min for 2h, and after the ball milling is completed, a composite solution based on boron is obtained; S12, sodium silicate solution and hydroxyapatite are added to the sodium alginate solution and stirred uniformly to obtain a sodium alginate agent; 3 parts of barium sulfate, 2 parts of mica powder and 5 parts of sodium alginate agent are stirred fully, then filtered and dried to obtain a blending additive; S13, the composite solution based on boron and the blending additive are mixed according to a weight ratio of 7:5 and subjected to ball milling treatment at a ball milling speed of 1500r / min for 2h, and after the ball milling is completed, the mixture is filtered and dried to obtain a blending agent based on boron addition.

[0035] The mass fraction of the yttrium nitrate solution in the embodiment is 2%; the mass fraction of the sodium alginate solution is 5%; and the mass fraction of the sodium silicate solution is 4%.

[0036] The mass ratio of the sodium alginate solution, the sodium silicate solution and the hydroxyapatite in the embodiment is 8:4:3.

[0037] The preparation method of the high-temperature impact-resistant flux-cored wire of the embodiment is used to prepare the flux-cored wire. The preparation method of the high-temperature impact-resistant flux-cored wire of the embodiment comprises the following steps: Step one: the raw materials are weighed according to the weight parts: chromium carbide powder 6 parts, molybdenum powder 9 parts, nickel powder 8 parts, niobium powder 15 parts, tungsten carbide powder 18 parts, modified titanium carbide agent 11 parts, blending agent based on boron addition 8 parts, 30 mesh natural graphite 4 parts, sodium fluorosilicate 2 parts, aluminum powder 2 parts and iron powder 75 parts; Step two: first add chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder, modified titanium carbide agent, blending agent based on boron addition, 30 mesh natural graphite and iron powder into a double-cone mixer, mix at low speed for 40 min, mixing speed 150 r / min, then add sodium fluorosilicate and aluminum powder, mix at high speed for 20 min, mixing speed 850 r / min, and argon gas is introduced during the mixing process for protection; Step three: fill the mixed core powder of step two into a U-shaped steel belt slot, control the core filling rate to be 42%, and immediately roll into shape after filling; Step four: then use drawing treatment, and finally dry the drawn welding wire in a vacuum oven at 125°C for 3h.

[0038] The drawing treatment of this embodiment adopts 10 passes, and the deformation rate of each pass is 12%, and the finished product diameter is 1.2mm.

[0039] The preparation method of the modified titanium carbide agent of this embodiment is: S01, preparation of the modification liquid: S02, preheat the titanium carbide at 60°C for 1h to obtain preheated titanium carbide, and then stir and modify the preheated titanium carbide and the modification liquid according to a weight ratio of 3:8, and obtain the titanium carbide modification liquid after stirring is completed; S03, stir the basalt fiber in a sufficient amount of 15% mass fraction potassium permanganate solution, then wash with water, filter and dry; Blend 5 parts of dried basalt fiber, 4 parts of mullite whiskers and 3 parts of wollastonite with 15 parts of sodium lignosulfonate solution, then filter and dry to obtain a basalt fiber filler; S04, ball mill the titanium carbide modification liquid and the basalt fiber filler according to a weight ratio of 11:5, the ball milling speed is 1500 r / min, and the ball milling time is 2h, then filter and dry to obtain the modified titanium carbide agent.

[0040] The stirring speed of the stirring modification treatment of this embodiment is 550 r / min, and the stirring time is 2h; the mass fraction of the sodium lignosulfonate solution is 15%.

[0041] The preparation method of the modification liquid of this embodiment is: S01a, blend and sinter 8 parts of silicon dioxide, 5 parts of petalite and 4 parts of nano lanthanum oxide, and obtain a sintered body after sintering is completed; Blend 5 parts of silicon dioxide, 5 parts of petalite and 4 parts of nano lanthanum oxide, and obtain a sintered body after sintering is completed; S01b, blend 8 parts of sodium citrate solution, 3 parts of zinc oxide and 0.5 parts of nano silicon sol uniformly, then add 5 parts of silane coupling agent-β cyclodextrin agent and continue to blend thoroughly to obtain a modified sodium citrate solution; S01c, the sintered body, the modified sodium citrate solution is stirred uniformly according to the weight ratio of 5:11 to obtain a modified solution.

[0042] The sintering time of the blended sintered body of this embodiment is 1.5h, and the sintering temperature is 350℃.

[0043] The preparation method of the blending additive based on boron addition of this embodiment is: S11, 5 parts of yttrium nitrate solution, 4 parts of carbon nanotubes and 3 parts of titanium oxide are uniformly blended, then 40% of the total amount of the blended material is added to the blended material, ball milling treatment, ball milling speed 1500r / min, ball milling 2h, after ball milling, a boron-based composite solution is obtained; S12, the sodium alginate solution is stirred uniformly by adding sodium silicate solution and hydroxyapatite to obtain a sodium alginate agent; 5 parts of barium sulfate, 4 parts of mica powder and 9 parts of sodium alginate agent are stirred thoroughly, then filtered and dried to obtain a blending additive; S13, the boron-based composite solution and the blending additive are mixed according to the weight ratio of 11:5 and ball milled, the ball milling speed is 1700r / min, the ball milling time is 2h, after ball milling, the mixture is filtered and dried to obtain a blending additive based on boron addition.

[0044] The mass fraction of the yttrium nitrate solution of this embodiment is 5%; the mass fraction of the sodium alginate solution is 7%; and the mass fraction of the sodium silicate solution is 6%.

[0045] The mass ratio of the sodium alginate solution, the sodium silicate solution and the hydroxyapatite of this embodiment is 12:7:3.

[0046] The preparation method of the high-temperature impact-resistant flux-cored wire of this embodiment is used to prepare the flux-cored wire. Embodiment 3. The preparation method of the high-temperature impact-resistant flux-cored wire of this embodiment comprises the following steps: Step one: weigh the raw materials according to the weight parts: chromium carbide powder 5 parts, molybdenum powder 8 parts, nickel powder 7 parts, niobium powder 12.5 parts, tungsten carbide powder 16.5 parts, modified titanium carbide agent 9 parts, blending additive based on boron addition 6.5 parts, 30 mesh natural graphite 3 parts, sodium fluosilicate 1.5 parts, aluminum powder 1.5 parts and iron powder 72.5 parts; Step two: first, add chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder, modified titanium carbide agent, blending additive based on boron addition, 30 mesh natural graphite and iron powder into a double-cone mixer, mix at low speed for 35min, mixing speed 125r / min, then add sodium fluosilicate and aluminum powder, mix at high speed for 17.5min, mixing speed 800r / min, and argon gas is introduced for protection during the mixing process; Step three: fill the mixed core powder of step two into the U-shaped steel belt slot, control the core filling rate to be 40%, and immediately roll into shape after filling; Step four: further adopt drawing treatment, and finally dry the drawn welding wire in a vacuum oven at 122 DEG C for 2.5 h.

[0047] The drawing treatment of the embodiment adopts 10 passes, and the deformation rate of each pass is 12%, and the diameter of the finished product is 1.2 mm.

[0048] The preparation method of the modified titanium carbide agent of the embodiment is: S01, preparation of the modified liquid: S02, preheat the titanium carbide at 58 DEG C for 1 h to obtain preheated titanium carbide, and stir and modify the preheated titanium carbide and the modified liquid according to a weight ratio of 3:6.5, and obtain a titanium carbide modified liquid after stirring. S03, stir the basalt fiber in a sufficient amount of 12.5% mass fraction potassium permanganate solution, then wash with water, filter and dry; Blend 4 parts of dried basalt fiber, 3 parts of mullite whisker and 2.5 parts of wollastonite with 12.5 parts of sodium lignosulfonate solution, then filter and dry to obtain a basalt fiber filler. S04, ball mill the titanium carbide modified liquid and the basalt fiber filler according to a weight ratio of 9:5, the ball milling speed is 1250 r / min, and the ball milling time is 2 h, then filter and dry to obtain a modified titanium carbide agent.

[0049] The stirring speed of the stirring modification treatment of the embodiment is 500 r / min, and the stirring time is 2 h; the mass fraction of the sodium lignosulfonate solution is 12.5%.

[0050] The preparation method of the modified liquid of the embodiment is: S01a, blend and sinter 6.5 parts of silicon dioxide, 4 parts of petalite and 3 parts of nano lanthanum oxide, and obtain a sintered body after sintering; Blend 3 parts of silane coupling agent KH550, 1 part of β-cyclodextrin and 6 parts of 80% mass fraction ethanol solution to obtain a silane coupling agent-β-cyclodextrin agent; S01b, blend 6.5 parts of sodium citrate solution, 2.5 parts of zinc oxide and 0.4 parts of nano silicon sol uniformly, then add 4 parts of silane coupling agent-β-cyclodextrin agent and continue to blend to obtain a modified sodium citrate solution; S01c, blend the sintered body and the modified sodium citrate solution according to a weight ratio of 5:9 to obtain a modified liquid.

[0051] The sintering time of the blend sintering of the embodiment is 1.25 h, and the sintering temperature is 325 DEG C.

[0052] The preparation method of the boron-based blending agent of the embodiment is as follows: S11, 4 parts of yttrium nitrate solution, 3 parts of carbon nanotubes and 2 parts of titanium oxide are uniformly blended, then 37.5% of the total amount of the blended material is added to the blended material, ball milling treatment, ball milling speed 1250r / min, ball milling for 2h, after ball milling, a boron-based composite liquid is obtained; S12, the sodium alginate solution is stirred uniformly by adding sodium silicate solution and hydroxyapatite, and a sodium alginate agent is obtained; 4 parts of barium sulfate, 3 parts of mica powder and 6.5 parts of sodium alginate agent are stirred thoroughly, then filtered and dried to obtain a blending additive; S13, the boron-based composite liquid and the blending additive are mixed and ball milled according to a weight ratio of 9:5, the ball milling speed is 1600r / min, the ball milling time is 2h, after ball milling, the mixture is filtered and dried to obtain a boron-based blending agent.

[0053] The mass fraction of the yttrium nitrate solution of the embodiment is 3.5%; the mass fraction of the sodium alginate solution is 6%; and the mass fraction of the sodium silicate solution is 5%.

[0054] The mass ratio of the sodium alginate solution, the sodium silicate solution and the hydroxyapatite of the embodiment is 10:5.5:3.

[0055] The preparation method of the high-temperature impact-resistant flux-cored wire of the embodiment is used to prepare a flux-cored wire. Different from Example 3 is that no modified titanium carbide agent is added.

[0056] Comparative Example 2. Different from Example 3 is that no basalt fiber filler is added in the preparation of the modified titanium carbide agent.

[0057] Comparative Example 3. Different from Example 3 is that no dried basalt fiber and mullite whisker is added in the preparation of the basalt fiber filler.

[0058] Comparative Example 4. Different from Example 3 is that no wollastonite is added in the preparation of the basalt fiber filler.

[0059] Comparative Example 5. Different from Example 3 is that no titanium carbide modification liquid is added in the preparation of the modified titanium carbide agent.

[0060] Comparative Example 6. Different from Example 3 is that the titanium carbide modification liquid is not treated by the modification liquid.

[0061] Comparative Example 7. Different from Example 3 is that no boron-based blending agent is added.

[0062] Comparative Example 8. The difference between Example 3 is that the boron-based complexing liquid is not added in the preparation of the blending agent based on boron addition.

[0063] Comparative Example 9. The difference between Example 3 is that the carbon nanotubes and titanium oxide are not added in the preparation of the boron-based complexing liquid.

[0064] Comparative Example 10. The difference between Example 3 is that the boron oxide is not added in the preparation of the boron-based complexing liquid.

[0065] Comparative Example 11. The difference between Example 3 is that the blending additive is not added in the preparation of the blending agent based on boron addition.

[0066] Comparative Example 12. The difference between Example 3 is that the barium sulfate, mica powder is not added in the blending additive.

[0067] Comparative Example 13. The difference between Example 3 is that the sodium alginate agent is not added in the blending additive.

[0068] The flux-cored wires of the products of Examples 1-3 and Comparative Examples 1-13 are welded with stainless steel plates as the base material, and then the performance of the weld is tested, including impact resistance, weld tensile strength, high temperature resistance of the product at 850, 950℃ respectively for 48h, and low temperature freezing stability (the product is placed at-40℃ for 5d). The test results are shown in Table 1 below. Table 1: From Comparative Examples 1-13 and Examples 1-3, it can be seen that: The product of Example 3 has excellent impact resistance, weld tensile strength, and excellent high temperature resistance and low temperature freezing stability at 850, 950℃. From Comparative Examples 1-13 and Example 3, it can be seen that when one of the modified titanium carbide agent and the blending agent based on boron addition is not added, the performance of the product is significantly poorer, and when both are used, the performance of the product is the most significant. The basalt fiber filler is not added in the preparation of the modified titanium carbide agent, the dry basalt fiber and mullite whisker are not added in the preparation of the basalt fiber filler, the wollastonite is not added in the preparation of the basalt fiber filler, the titanium carbide modification liquid is not added in the preparation of the modified titanium carbide agent, the titanium carbide modification liquid is not treated by the modification liquid, the performance of the product has a deterioration trend, the basalt fiber filler prepared by the specific method of the application is combined with the titanium carbide modification liquid to form the modified titanium carbide agent, the performance of the product is most remarkable, and the titanium carbide modification liquid is not treated by the modification liquid, the performance of the product has a large change trend, the titanium carbide modification liquid treated by the modification liquid has a large influence trend on the performance of the product. The boron-based composite liquid is not added in the preparation of the blending agent based on boron addition, the carbon nanotube and titanium oxide are not added in the preparation of the boron-based composite liquid, the boron oxide is not added in the preparation of the boron-based composite liquid, the blending additive is not added in the preparation of the blending agent based on boron addition, the barium sulfate and mica powder are not added in the blending additive, the sodium alginate agent is not added in the blending additive, the performance of the product has a deterioration trend, only the blending agent based on boron addition prepared by the method of the application has the most remarkable performance effect, and the effect is not obvious when other methods are used instead; the preparation of the boron-based composite liquid and the blending additive has specificity, and only the raw materials used in the application have the most remarkable performance effect.

[0069] The application further explores the performance of the product through the preparation of the modification liquid. Experimental example 1. The same as example 3, except that the sintered body is not added in the modification liquid.

[0070] Experimental example 2. The same as example 3, except that the nano lanthanum oxide is not added in the sintered body.

[0071] Experimental example 3. The same as example 3, except that the silicon dioxide and petalite are not added in the sintered body.

[0072] Experimental example 4. The same as example 3, except that the silane coupling agent-beta cyclodextrin agent is not added in the modified sodium citrate liquid.

[0073] Experimental example 5. The same as example 3, except that the zinc oxide and nano silicon sol are not added in the modified sodium citrate liquid.

[0074] The application further tests the performance of the products of experimental examples 1-5, and the performance test is shown in the following table 2, which is the performance influence test of the preparation of the modification liquid on the product, as shown in the following table 2. Table 2: From experimental examples 1-5, it can be seen that the sintered body is not added in the modified liquid, in the preparation factors of the modified liquid, the product performance is the most obvious, the sintered body is not added with nano lanthanum oxide, the sintered body is not added with silicon dioxide and petalite, the product performance has a deterioration trend, at the same time, the modified sodium citrate liquid is not added with silane coupling agent-beta cyclodextrin agent, the modified sodium citrate liquid is not added with zinc oxide and nano silicon sol, the product performance also has a deterioration trend, only the modified liquid prepared by the specific method of the application has the most significant product performance effect, in the preparation of the modified liquid, the raw materials are indispensable, only the specific raw material ratio of the application is adopted, other raw material ratios are not as significant as the effect of the application.

[0075] It will be obvious to a person skilled in the art that, without departing from the spirit or essential characteristics of the application, the application can be implemented in other specific forms. The present embodiments are therefore to be considered in all respects as illustrative and not restrictive, the scope of the application being indicated by the appended claims rather than by the specification as a whole, and all changes which come within the meaning and range of equivalency of the claims are therefore intended to be embraced therein.

[0076] Furthermore, it should be understood that, although the present specification is described in terms of embodiments, not every embodiment exhibits every characteristic or exhibits the characteristics in the same way. The description herein of any particular embodiment is primarily intended to enable persons skilled in the art to make and use any of the embodiments as claimed. Any combination of any of the features described herein is specifically contemplated and may be claimed.

Claims

1. A method of making a high impact temperature resistant flux cored welding wire, characterized by, The method comprises the following steps: Step 1: ingredients are weighed according to weight parts: chromium carbide powder 4-6 parts, molybdenum powder 7-9 parts, nickel powder 6-8 parts, niobium powder 10-15 parts, tungsten carbide powder 15-18 parts, modified titanium carbide agent 7-11 parts, blending agent based on boron addition 5-8 parts, 30 mesh natural graphite 2-4 parts, sodium fluosilicate 1-2 parts, and aluminum powder 1-2 parts, and iron powder 70-75 parts; Step 2: chromium carbide powder, molybdenum powder, nickel powder, niobium powder, tungsten carbide powder, modified titanium carbide agent, blending agent based on boron addition, 30 mesh natural graphite, and iron powder are added to a double-cone mixer, mixed at low speed for 30-40 minutes, and mixed at a speed of 100-150 r / min, then sodium fluosilicate and aluminum powder are added, mixed at high speed for 15-20 minutes, and mixed at a speed of 750-850 r / min, and argon gas is introduced during the mixing process; Step 3: the mixed core powder of step 2 is filled into a U-shaped steel belt slot, and the core filling rate is controlled to be 38-42%, and then the filling is immediately rolled into a shape; Step 4: then, drawing treatment is adopted, and finally, the drawn welding wire is dried in a vacuum oven at 120-125 DEG C for 2-3 hours.

2. The method of claim 1, wherein the flux-cored welding wire is prepared by the steps of: The drawing treatment adopts 10 passes, and the deformation rate of each pass is 12%, and the diameter of the finished product is 1.2 mm. ​ 3. The method of claim 1, wherein the flux-cored welding wire has a tensile strength of 500 MPa or more, an impact strength of 20 J or more at 23°C, and an impact strength of 10 J or more at -40°C. The preparation method of the modified titanium carbide agent is: S01, preparation of a modification liquid: S02, titanium carbide is preheated at 55-60 DEG C for 1 hour to obtain preheated titanium carbide, and the preheated titanium carbide and the modification liquid are stirred and modified according to a weight ratio of 3:(5-8), and after stirring, a titanium carbide modification liquid is obtained; S03, basalt fibers are stirred in a sufficient amount of 10-15% mass fraction potassium permanganate solution, then washed with water, filtered, and dried; 3-5 parts of dried basalt fibers, 2-4 parts of mullite whiskers, and 2-3 parts of wollastonite are blended with 10-15 parts of a sodium lignosulfonate solution, then filtered and dried to obtain a basalt fiber filler; S04, the titanium carbide modification liquid and the basalt fiber filler are ball milled according to a weight ratio of (8-11):5, the ball milling speed is 1000-1500 r / min, and the ball milling time is 2 hours, then the ball milling is completed, and the mixture is filtered and dried to obtain a modified titanium carbide agent.

4. The method of claim 3, wherein the flux-cored welding wire is prepared by the steps of: The stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 2 hours; and the mass fraction of the sodium lignosulfonate solution is 10-15%. ​ 5. The method of claim 3, wherein the flux-cored welding wire is prepared by the steps of: The preparation method of the modification liquid is: ​ S01a, 5-8 parts of silicon dioxide, 3-5 parts of petalite, and 2-4 parts of nano lanthanum oxide are blended and sintered, and after sintering, a sintered body is obtained; A silane coupling agent-beta cyclodextrin agent is obtained by blending silane coupling agent KH550, beta cyclodextrin, and 75-85% mass fraction ethanol solution according to a weight ratio of (2-4):1:(5-7); S01b, 5-8 parts of sodium citrate solution, 2-3 parts of zinc oxide, and 0.3-0.5 parts of nano silicon sol are uniformly blended, then 3-5 parts of silane coupling agent-beta cyclodextrin agent is added and blended to obtain a modified sodium citrate solution. S01c, the sintered body, modified sodium citrate solution according to the weight ratio 5: (8-11) stirring, the modified liquid.

6. The method of claim 5, wherein the flux core wire is prepared by the steps of: The sintering time of the blended sintered body is 1-1.5h, and the sintering temperature is 300-350℃. ​ 7. The method of claim 1, wherein the flux-cored welding wire has a tensile strength of 100,000 psi or more, a yield strength of 80,000 psi or more, and a 2% offset yield strength of 70,000 psi or more. The preparation method of the blending agent based on boron addition is: S11, 3-5 parts of yttrium nitrate solution, 2-4 parts of carbon nanotubes and 1-3 parts of titanium oxide are uniformly blended, then 35-40% of boron oxide of the total amount of the blended material is added to the blended material, ball milling treatment, ball milling speed 1000-1500r / min, ball milling 2h, after ball milling, to obtain a boron-based composite liquid; S12, the sodium alginate solution is added to the sodium alginate solution and hydroxyapatite and stirred uniformly to obtain a sodium alginate agent; 3-5 parts of barium sulfate, 2-4 parts of mica powder and 5-9 parts of sodium alginate agent are stirred fully, then filtered and dried to obtain a blending additive; S13, the boron-based composite liquid and the blending additive are mixed according to the weight ratio (7-11):5 and ball milled, the ball milling speed is 1500-1700r / min, the ball milling time is 2h, after ball milling, the mixture is filtered and dried to obtain a blending agent based on boron addition.

8. The method of claim 7, wherein the flux-cored welding wire is prepared by the steps of: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 5-7%; and the mass fraction of the sodium silicate solution is 4-6%. ​ 9. The method of claim 7, wherein the flux-cored welding wire is prepared by the steps of: The mass ratio of the sodium alginate solution, the sodium silicate solution and the hydroxyapatite is (8-12):(4-7):

3. ​ 10. The flux-cored wire prepared by the preparation method of the flux-cored wire according to any one of claims 1-9.

Citation Information

Cited By

  • Preparation method for manufacturing welding wire by using steel wire rope

    CN121870344A

  • A method of making a welding wire from a steel wire cable

    CN121870344B